Materiality: stakeholder accountability choices in hotels’ sustainability reports (2019)
Purpose: This paper aims to examine the choices made by the hotel industry about what to include, and who to be accountable to, in their sustainability reports; a process defined as materiality assessment. Design/methodology/approach: The paper is based on the findings of semi-structured interviews with eight sustainability managers (from eight of the world’s 50 largest hotel groups) to explore their understanding of, and use of, materiality and any barriers to its uptake and eight industry sustainability experts to assess the general industry-wide application of materiality. Findings: Sustainability managers from large hotel groups are evasive when disclosing their materiality criteria, their decision-making processes and how they aggregate stakeholder feedback; they limit their disclosure to the reporting process. Sustainability managers are disempowered, with limited resources, time, knowledge and skills to apply to materiality assessment. Experts confirm that hotel groups are unsystematic and opaque about their decision-making and how they control their materiality assessments. Practical implications: Materiality assessment is concealed from the public and may be constructed around business imperatives with high managerial capture. The hospitality industry needs to improve its sustainability reporting by examining how it defines and applies materiality and by addressing the barriers identified, if it is to demonstrate an enduring commitment to sustainability and organisational legitimacy. Originality/value: This study addresses the limited knowledge of how hotel groups undertake materiality assessments. It identifies gaps in the conception and application of materiality by pinpointing barriers to its uptake and recommending areas in need of further research. © 2019, Emerald Publishing Limited.